Intra-articular botulinum toxin a (Bont/a) for pain management in dogs with osteoarthritis secondary to hip dysplasia: A randomized controlled clinical trial - Nicácio, Gabriel Montoro; Luna, Stelio Pacca Loureiro [UNESP]; Cavaleti, Poliana; Cassu, Renata Navarro (Japanese Society of Veterinary Science, 2019)
The aim of this study was to evaluate the efficacy and safety of the intra-articular (IA) injection of botulinum toxin type A (BoNT/A) to the management of chronic pain in dogs. In a randomized, controlled, double-blinded study sixteen dogs with osteoarthritis secondary to hip dysplasia were distributed into two groups: 25 IU BoNT/A (BoNT) or saline solution (Control) was administered IA in each affected joint. All dogs received oral supplements (90 days) and carprofen (15 days). The dogs were assessed by a veterinarian on five occasions and the owner completed aassessment form at the same time (baseline to 90 days). The data were analyzed using unpaired-t test, Fisher’s exact test, analysis of variance and the Tukey’s test (P<0.05). There were no differencebetween groups in the veterinarian and owner assessments. Lower scores were observed in both groups during 90 days after IA therapy in the owner assessments (P<0.001). Compared with baseline, the Vet score was lower from 15–90 days after IA injection in the BoNT group, and at 15 and 30 days in the Control group (P<0.001). Both treatments were safe and reduced the clinical signs associated with hip osteoarthritis. However, IA BoNT/A (25 IU) did not provide better pain relief than the control treatment.
Keywords: Analgesia; Botulinum toxin; Canine; Osteoarthritis; Supplement